2019
DOI: 10.1016/j.neuropharm.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Roles of K+ and cation channels in ORL-1 receptor-mediated depression of neuronal excitability and epileptic activities in the medial entorhinal cortex

Abstract: Nociceptin (NOP) is an endogenous opioid-like peptide that selectively activates the opioid receptor-like (ORL-1) receptors. The entorhinal cortex (EC) is closely related to temporal lobe epilepsy and expresses high densities of ORL-1 receptors. However, the functions of NOP in the EC, especially in modulating the epileptiform activity in the EC, have not been determined. We demonstrated that activation of ORL-1 receptors remarkably inhibited the epileptiform activity in entorhinal slices induced by applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 117 publications
(150 reference statements)
0
11
0
Order By: Relevance
“…2017; Li et al . 2019), we included 300 µ m Ba 2+ in the extracellular solution to inhibit Kir channels. Bath application of 300 µ m Ba 2+ indeed inhibited a current showing inward rectification ( n = 14, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2017; Li et al . 2019), we included 300 µ m Ba 2+ in the extracellular solution to inhibit Kir channels. Bath application of 300 µ m Ba 2+ indeed inhibited a current showing inward rectification ( n = 14, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To prevent potential desensitization induced by repeated applications of the agonist, one slice was limited to only one application of TGOT. Frequency of APs was calculated by Mini Analysis 6.0.1 (Synaptosoft Inc., Decatur, GA, USA), as described previously (Li et al 2019). Resting membrane potentials (RMPs) and holding currents (HCs) at −60 mV were recorded in the extracellular solution supplemented with tetrodotoxin (TTX, 0.5 µM), kynurenic acid (1 mM) and picrotoxin (100 µM).…”
Section: Recordings Of Action Potentials Resting Membrane Potentials and Holding Currents From Amygdala Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular K + dynamics are determined by the rate of active K + uptake into nearby astrocytes, as well as the rate of extracellular diffusion [ 67 ]. If not cleared, increased extracellular K + can lead to altered network oscillations and ictal activity [ 66 , 68 ]. Previous reports suggested that the rate of K + clearance can also be affected by different factors, including temperature [ 32 ], ammonia [ 69 ], glutamate [ 40 ], and pH, however, the cellular mechanisms affecting this clearance process are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We used a voltage clamp and recorded the holding currents at −60 mV in response to bath application of AVP. Bath application of AVP induced an inward holding current in K + -gluconate-containing intracellular solution (−15.9 ± 3.2 pA, n = 14, p = .0002 vs. baseline, Wilcoxon test; Figure 7 Micromolar concentration of Ba 2+ (100-300 μM) has been shown to block Kir channels by at least 80% (Hu et al, 2017;Lacey et al, 1988;Li et al, 2019). We thus included 300 μM Ba 2+ in the extracellular solution to inhibit Kir channels and tested the effects of Ba 2+ on AVP-induced inward currents.…”
Section: Avp Excites Ca1 Pyramidal Neurons By Depressing An Inwardly Rectifying K + Channelmentioning
confidence: 98%